Literature Review -6σ DMAIC (An Acronym For Define, Measure, Analyze, Improve & Control) - Singh, Vikram; Arora, Aman; Sharma, Himanshu (International Journal of Computer Sciences and Engineering, 2025)
Today, the manufacturing industry is changing rapidly in the economic situation. Due to globalization, the manufacturing industry is facing global competition in this scenario. The major problems facing these industries are the decline in profit margins, the demand for customers for high quality products and product diversity is declining. Today there is high pressure on the manufacturing industry of every short time. TQM, JIT MRP-I, MRP-II, Lean Management, ISO standards, Kaizen are some such industrial engineering and quality management strategies that have been developed to answer the requirements of broad competition. A very latest and powerful philosophy of this field is 6σ in the manufacturing sector around the world, 6σ is becoming very popular and it is being used to improve production rate and quality performance as well as for quality variations. It is also being taken to strengthen the Tea Paper Automobile Industries, small-scale industries, service industries and products. Imran provides a review of studies of 6σ terms applicable industries.